Relationship between small for gestational age and aortic intima-media thickness in newborns - Alfarizi, Ahmad Bayu; Nova, Ria; Tasli, Julniar Mawardi; Theodorus, Theodorus (Paediatrica Indonesiana, 2014)
Background Small for gestational age (SGA) has been associated with adult cardiovascular disease. Small for gestational age newborns may undergo early aortic wall intima-media thickening (aIMT) in utero. Objective To determine the relationship between SGA as a risk factor for increased aIMT, as a sign of atherosclerosis onset. Methods We conducted a case-control study in the Neonatal Ward and Rooming-in Nursery at Dr. Mohammad Hoesin Hospital, Palembang, between April to June 2012. Subjects were allocated to either the case group (aIMT 2: 0.9 mm) or to the control group (aIMT <0.9 mm). Newborns were classified as SGA if their birthweight (BW) was < l O'h percentile, and appropriate for gestational age (AGA) if their BW was between lQth - 90'h percentile, according to the Lubchenco curve. Abdominal aortic intima-media thickness was measured by echocardiography examination. Results The case and control groups consisted of 30 n ewborns each. The proportion of SGA newborns was higher in the case group than the control group. The likelihood of infants in the case group being SGA was significantly higher compared to the control group, with odds ratio of 10.8 (95%CI 3,26 to 35, 72) . The mean aIMT was significantly higher in SGA than in AGA infants, 0.9 (SD 0.16) mm vs. 0.8 (SD 0.13) mm, respectively, with a mean difference of 0, 13 (9 5% CI 0, 050 to 0,209 mm; P"" 0,02). Conclusion Increased aIMT is more likely found in SGA newborns.